Structural Basis for GTP-Dependent Dimerization of Hydrogenase Maturation Factor HypB - Chan, Kwok-Ho; Li, Ting; Wong, Ching-On; Wong, Kam-Bo (PLOS ONE, 2012)
Maturation of [NiFe]-hydrogenase requires the insertion of iron, cyanide and carbon monoxide, followed by nickel, to the catalytic core of the enzyme. Hydrogenase maturation factor HypB is a metal-binding GTPase that is essential for the nickel delivery to the hydrogenase. Here we report the crystal structure of Archeoglobus fulgidus HypB (AfHypB) in apo-form. We showed that AfHypB recognizes guanine nucleotide using Asp-194 on the G5 loop despite having a non-canonical NKxA G4-motif. Structural comparison with the GTPγS-bound Methanocaldococcus jannaschii HypB identifies conformational changes in the switch I region, which bring an invariant Asp-72 to form an intermolecular salt-bridge with another invariant residue Lys-148 upon GTP binding. Substitution of K148A abolished GTP-dependent dimerization of AfHypB, but had no significant effect on the guanine nucleotide binding and on the intrinsic GTPase activity. In vivo complementation study in Escherichia coli showed that the invariant lysine residue is required for in vivo maturation of hydrogenase. Taken together, our results suggest that GTP-dependent dimerization of HypB is essential for hydrogenase maturation. It is likely that a nickel ion is loaded to an extra metal binding site at the dimeric interface of GTP-bound HypB and transferred to the hydrogenase upon GTP hydrolysis.